Leitura recombinativa generalizada após procedimentos de correção com fading em pessoas com atraso no desenvolvimento cognitivo - ALVES, Keila Regina Sales (2008)
Several studies have investigated the use of correction procedures, such as copy exercises, dictates, and oralization in promoting recombinative reading in people with some or no cognitive developmental deficit. The use of supporting techniques, such as fading, have not been tested as another variable that could immediately favor generalized recombinative reading. This work reports two studies. Study one, which included two students with cognitive developmental deficit, was divided in two stages. In Condition A, students were taught the relationships among spoken and printed words (AC), followed by equivalence tests among figures and printed words (BC), and printed words and figures (CB). Following those tests, reading tests about the taught words (MALA, PATO and BOCA) and generalized words (built up from the recombination among syllables) were used. Participants showed the reading of words only after formation of equivalence classes among figures, spoken words and printed have been documented. Afterwards, control probes used for syllable units and then a correction procedure was implemented, highlighting specific syllables (those identified after control probes have been used for syllable units) during copy, dictate and oralization combined teaching. Following four expositions to the correction procedure, participants were still showing only the reading of the words. In Condition B, fading in the specific syllables was introduced for the correction procedure. Participant MAR demonstrated a correct reading of all generalized words after the second use of the correction procedure, while participant CLA only after its third use. Participants showed function transference to new verbal forms AB, AC, BC, CB, AB, AC, BC and CB. These results indicated the need to evaluate the two correction procedures separately. In Study 2, two participants with cognitive developmental deficit were selected and subjected to the same experimental design used in Study 1. One participant was subjected to the correction procedure and the other to the fading in correction procedure. Participant FER was subjected to fading in correction procedure, while participant JOS to correction procedure highlighting syllables. Both participants showed generalized recombinative reading after fading in correction procedure, as well as function transference to new verbal forms AB, AC, BC, CB, AB, AC, BC and CB. The results indicate that fading in procedure immediately favor generative recombinative reading in people with cognitive developmental deficit.